2009
DOI: 10.1021/ja909030c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Enantioselective Addition of Two Distinct Nucleophiles across Alkenes Capable of Quinone Methide Formation

Abstract: A sequential intramolecular-intermolecular enantioselective alkene difunctionalization reaction has been developed which is thought to proceed through Pd-catalyzed quinone methide formation. The synthesis of new chiral heterocyclic compounds with adjacent chiral centers is achieved in enantiomeric ratios up to 99:1 and diastereomeric ratios up to 10:1.The formation of two carbon-heteroatom bonds across an alkene is a process which rapidly increases molecular complexity. The osmium-catalyzed Sharpless dihydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(48 citation statements)
references
References 30 publications
0
42
0
6
Order By: Relevance
“…An initial mechanistic investigation with the genminally dimethylated substrate 170 led to a product 171 without any detectable enantiomeric excess. This result suggested that the enantioselectivity is generated within the initial alkoxypalladation followed by faster palladium loss from the corresponding quinone methide intermediate than subsequent diastereoselective nucleophilic methoxide addition to the free quinone methide intermediate AM [114]. An extensive mechanistic investigation including kinetic analyses and electronic effects regarding the substrate substitution suggested that the reaction proceeds under nucleopalladation followed by turnover limiting addition of methoxide to the intermediary quinone methide [115].…”
Section: Chlorohydrin Synthesis and Vicinal Dibrominationmentioning
confidence: 99%
“…An initial mechanistic investigation with the genminally dimethylated substrate 170 led to a product 171 without any detectable enantiomeric excess. This result suggested that the enantioselectivity is generated within the initial alkoxypalladation followed by faster palladium loss from the corresponding quinone methide intermediate than subsequent diastereoselective nucleophilic methoxide addition to the free quinone methide intermediate AM [114]. An extensive mechanistic investigation including kinetic analyses and electronic effects regarding the substrate substitution suggested that the reaction proceeds under nucleopalladation followed by turnover limiting addition of methoxide to the intermediary quinone methide [115].…”
Section: Chlorohydrin Synthesis and Vicinal Dibrominationmentioning
confidence: 99%
“…Sigman et al [208,209] developed a highly enantioselective Pdcatalyzed alkene difunctionalization reaction involving the addition of two distinct nucleophiles, a process which allows for the formation of complex chiral molecules from relatively simple starting materials. Under this strategy, Pd-catalyzed alkene difunctionalization can also proceed by intramolecular oxypalladation followed by the addition of nucleophiles such as methanol, n-butanol, benzyl alcohol, trimethylsilylethanol, (−)-myrtenol, azide, and indole to a quinone methide (Scheme 102).…”
Section: Introductionmentioning
confidence: 99%
“…(1)]. [1] Methoden für Dioxygenierungen, [2] Diaminierungen [3] und Oxyaminierungen [4] wurden beschrieben. Im Vergleich zu Difunktionalisierungen, bei denen zwei Heteroatom-Gruppen an das Olefin addiert werden, sind intermolekulare metallvermittelte Carbofunktionalisierungen von Olefinen, auch unter Einbeziehung anderer Metalle als Palladium, selten [Gl.…”
unclassified
“…Im Vergleich zu Difunktionalisierungen, bei denen zwei Heteroatom-Gruppen an das Olefin addiert werden, sind intermolekulare metallvermittelte Carbofunktionalisierungen von Olefinen, auch unter Einbeziehung anderer Metalle als Palladium, selten [Gl. (2)]. [5][6][7] Wir präsentieren hier unsere Ergebnisse zu hoch stereoselektiven intermolekularen Pd-katalysierten Oxyarylierungen von Indenen mit verschiedenen Arylboronsäuren und dem 2,2,6,6-Tetramethylpiperidin-N-oxyl-Radikal [8] (TEMPO) als Oxidationsmittel und Reagens zur Synthese von 1,2,3-trisubstitutierten Indanen [Gl.…”
unclassified
See 1 more Smart Citation